PENGEMBANGAN MODEL PERANGKAT PEMBELAJARAN MENULIS LEGENDA DENGAN STRATEGI BELAJAR KUANTUM - Sukirno Sukirno (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2014)
Abstract: Developing Model To Teach A Legend Writing Using Quantum. The general problem of this research is that there is no teaching instrument model for a legend writing using quantum learning strategy. In accardance with the problem, the aim of this research is to develop a model for the teaching of a legend writing using quantum learning strategies. The results of this research are a book and electronic device. The model in the form of a book consists of three models, namely (1) syllabus model and learning evaluation system of a legend writing, (2) learning materials model of a legend writing, and (3) learning scenario model of a legend writing. The model in the form of an electronic device consists of a vcd containing the visualization of a legend writing materials. Based on the analysis of qualitative data, the three learning instrument models have the effectiveness in the main material part, learning experience, achevement indicator, evaluation system, and sourse part and the media used. Based on the analysis of quantitatif data, it is known that there is a difference of pre-test score and post-test score of a legend writing competence using convensional learning strategy, but such a difference is not a significant one (p > 0,005). On the other hand, the pre-test and post-test scores of a legend writing using quantum learning strategy has a significant defference (p < 0,001). Thus, the three models of learning instrument are proved effective and influence on the developmen of a legend writing competence. Key word: learning instrument model, legend writing, quantum learning strategy Abstrak: Masalah umum penelitian ini adalah belum ada model perangkat pembelajaran menulis legenda dengan strategi belajar kuantum. Sesuai dengan masalah tersebut, tujuan penelitian ini adalah menghasilkan model perangkat pembelajaran menulis legenda dengan strategi belajar kuantum. Hasil penelitian ini berbentuk buku dan elektronik. Model berbentuk buku terdiri atas tiga model, yaitu (1) model silabus dan sistem penilaian pembelajaran menulis legenda, (2) model bahan ajar pembelajaran menulis legenda, dan (3) model skenario pembelajaran menulis legenda. Model berbentuk elektronik berupa satu keping VCD berisi visualisasi materi pelajaran menulis legenda. Berdasarkan analisis data kualitatif, ketiga model perangkat pembelajaran tersebut memiliki keefektifan pada bagian materi pokok, pengalaman belajar, indikator pencapaian, sistem penilaian, dan bagian sumber serta media yang digunakan. Berdasarkan analisis data kuantitatif diketahui bahwa perbedaan skor tes awal dan tes akhir kemampuan menulis legenda dengan strategi belajar konvensional terdapat perbedaan, tetapi perbedaan itu tidak signifikan (p > 0,005). Sebaliknya, skor tes awal dan tes akhir kemampuan menulis legenda dengan strategi belajar kuantum terdapat perbedaan yang signifikan (p < 0,001). Jadi, ketiga model perangkat pembelajaran tersebut terbukti efektif dan berpengaruh terhadap peningkatan kemampuan menulis legenda. Kata kunci: model perangkat pembelajaran, menulis legenda, strategi belajar kuantum.